Urinary Frequency as a Presentation of Bulky Malignant Lymphoma in the Pelvis - Yasukazu Takase; Koichi Kodama; Isamu Motoi; Yasushi Terasaki; Katsuhiko Saito (Case Reports in Urology)
Malignant lymphomas may originate from any area of the body and cause a variety of symptoms. However, a malignant lymphoma causing urinary symptoms is uncommon. We report a unique case of a 77-year-old woman who presented with a persistent pollakiuria. Radiographic imaging showed a large pelvic mass ( cm) remarkably compressing and invading the bladder wall and accompanied with bilateral hydronephrosis. Urinary cytology revealed malignant lymphoma, and a final diagnosis of malignant lymphoma was made on the basis of transvaginal needle biopsy. Urinary cytology facilitated the definite diagnosis, following which we initiated a rapid and successful treatment with cyclophosphamide, doxorubicin, vincristine, and prednisone with rituximab.